Archives de la diplomatie linguistique : explorer les rôles des femmes pour réécrire l’histoire ? - Clémentine Rubio (Glad!)
This article identifies research perspectives with regards to women in archives of linguistic diplomacy. Based on the study of two types of archives, diplomatic archives form the French general consulate in Jerusalem and the archives of the "École de préparation des professeurs de français à l’étranger", this article examines the roles assigned to and played by women. This analysis draws upon effective traces of women in the archives and upon epistemological considerations concerning the creation of a narrative based on these traces and absences.